To Determine the Prevalence of Cysts and Tumors in Dental College (Academia Journal of Medicine, 2024)
This study aimed to ascertain the prevalence of cysts  and tumors among patients attending a dental  college. Utilizing retrospective data analysis, a  significant sample size was examined. Findings reveal  critical insights into occurrence rates, contributing to  improved diagnostic and therapeutic strategies within  the dental community.
Keywords: Cyst; tumor; prevalence; odontogenic cyst; treatment strategies